Weighted Bounded Solutions for a Class of Nonlinear Fractional Equations - Lizama-Yanez, C (Walter de Gruyter GmbH, 2016)
Let T be a bounded linear operator defined on a Banach space X. We investigate the existence of solutions for a class of nonlinear fractional equation in the form [Eqution presented here] on the vector-valued weighted sequence space [Eqution presented here] Our analysis relies on the fixed point theory and operator-theoretical methods. © 2016 Diogenes Co., Sofia.